2015
DOI: 10.1111/nph.13748
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of water and light availability after thinning at a xeric site: which matters more? A dual isotope approach

Abstract: SummaryThinning fosters individual tree growth by increasing the availability of water, light and nutrients. At sites where water rather than light is limiting, thinning also enhances soil evaporation and might not be beneficial. Detailed knowledge of the short-to long-term physiological response underlying the growth responses to thinning is crucial for the management of forests already suffering from recurrent drought-induced dieback.We applied a dual isotope approach together with mechanistic isotope models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
63
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 79 publications
(166 reference statements)
10
63
0
Order By: Relevance
“…At deeper soil depths, the amount and variations with age of SOC and available P were smaller than that at 0-5 cm depth, but available N that had very similar values across the entire soil profile and also followed the same trend with the superficial soil layer, as expected from the ability of this species capturing atmospheric N through its deep root system (Dzwonko and Loster, 1997;Von Holle et al, 2006). Soil moisture content showed a consistent decrease with age at all soil depths until maturity of plantations and then maintained a constant value, suggesting that the reduction in water consumption because of the decrease in tree density and canopy cover from age 30 was compensated by the increased growth of the remaining trees (Giuggiola et al, 2015). The use of true replicate plots for all ages and treatments in this research confirmed and broadened the previous findings that R. pseudoacacia reached their mature stage around age 30 in the Loess Plateau and that the impact on soil nutrients, soil moisture and PAR of these plantations intensified until the maturity of the plantations (Jin et al, 2011;Cheng et al, 2013Cheng et al, , 2014.…”
Section: Discussionsupporting
confidence: 68%
“…At deeper soil depths, the amount and variations with age of SOC and available P were smaller than that at 0-5 cm depth, but available N that had very similar values across the entire soil profile and also followed the same trend with the superficial soil layer, as expected from the ability of this species capturing atmospheric N through its deep root system (Dzwonko and Loster, 1997;Von Holle et al, 2006). Soil moisture content showed a consistent decrease with age at all soil depths until maturity of plantations and then maintained a constant value, suggesting that the reduction in water consumption because of the decrease in tree density and canopy cover from age 30 was compensated by the increased growth of the remaining trees (Giuggiola et al, 2015). The use of true replicate plots for all ages and treatments in this research confirmed and broadened the previous findings that R. pseudoacacia reached their mature stage around age 30 in the Loess Plateau and that the impact on soil nutrients, soil moisture and PAR of these plantations intensified until the maturity of the plantations (Jin et al, 2011;Cheng et al, 2013Cheng et al, , 2014.…”
Section: Discussionsupporting
confidence: 68%
“…In contrast to observations that show mitigating effects of shading, for example in the Mediterranean (Gómez‐Aparicio et al., ; Quero et al., ), our results demonstrate aggravated drought effects under moderate shading under the simulated future climatic conditions of the Central Alps. This result has important implications for the management of older and/or only slightly managed pine forests, where thinning may not only ameliorate soil water availability for adult trees by reducing competition with other plants (Flathers et al., ; Giuggiola et al., ) but also improve light conditions for pine regeneration. Even under future CO 2 enriched conditions, the growth of pine seedlings is more limited by light than water availability, which, in turn, confirms the wide regeneration niche of both P. sylvestris and P. nigra regarding soil water conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Seedlings were grown in moist and dry conditions (black and red symbols), ambient and elevated CO 2 (aCO 2 , eCO 2 ) and light and moderate shade (S 20 and S 40 , open and filled symbols, dashed and solid lines). Root biomass, root biomass fraction, vertical root length and specific vertical root length of dry × S 20 × eCO 2 seedlings was omitted due to May beetle grub infestation in the respective mesocosm (Flathers et al, 2016;Giuggiola et al, 2016) but also improve light conditions for pine regeneration. Even under future CO 2 enriched conditions, the growth of pine seedlings is more limited by light than water availability, which, in turn, confirms the wide regeneration niche of both P. sylvestris and P. nigra regarding soil water conditions.…”
Section: Con Clus Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Toward this end, a biophysical modeling approach has been used to estimate changes in drought stress due to stand occupancy and climate (Lutz, Wagtendonk, & Franklin, 2010). The effects of stand occupancy have also been demonstrated in reverse, where forest thinning has relieved drought stress and made stands more resistant to some beetle outbreaks (Bottero et al, 2017;Dore et al, 2012;Giuggiola et al, 2016;Hood et al, 2016;McDowell, Adams, Bailey, Hess, & Kolb, 2006;McDowell, Brooks, Fitzgerald, & Bond, 2003;Sohn, Saha, & Bauhaus, 2016;Vernon, Sherriff, Mantgem, & Kane, 2018;Waring & Pitman, 1985). Although previous studies have provided key insights on tree responses to stand occupancy, competition, and climate, there is a lack of direct evidence documenting the extent to which drought stress has tracked fire deficits following fire suppression efforts starting in the early 20th century.…”
Section: Introductionmentioning
confidence: 99%